A SULITNYA PROSES GUGAT CERAI ISTRI (ASN) PERSPEKTIF (MPU) ACEH TIMUR (Penelitian Kasus di Kecamatan Pereulak Kota Aceh) - Rasyidin; Manaf, Abdul; Rismaini (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study examines the process of divorce (talaq) undertaken by Civil Servants (Pegawai Negeri Sipil/PNS) in Peureulak Kota District and analyzes the views of the Aceh Ulama Consultative Council (Majelis Permusyawaratan Ulama/MPU) on the implementation of government regulations governing divorce permits for civil servants. The objectives of the study are to identify the constraints faced by PNS in obtaining divorce authorization and to assess the implications of these regulations for Islamic Family Law in Aceh, which is grounded in Sharia-based values. The research employs a qualitative methodology with a descriptive-analytical approach, utilizing interviews with village residents (warga gampong), tuha peut (members of the village consultative council), imum gampong (village imams), and geuchik (village heads). The findings indicate that although the grounds for divorce cited by civil servants meet the Sharia requirements, they nonetheless encounter significant difficulties in securing official permission from their superiors due to stringent administrative procedures. From the perspective of Islamic Family Law, this situation reflects an inherent tension between the individual right to initiate talaq and the state’s policy objective of safeguarding the public interest (maslahah ammah). The MPU Aceh maintains that such regulations are consistent with the principles of Maqasid al-Sharia, particularly the preservation of family integrity (hifz al-nasl) and social order (hifz al-mujtama). Accordingly, restrictions on divorce permits for civil servants may be understood as a form of tanzhimi (administrative regulation) intended to support the objectives of the Sharia in realizing justice and social welfare within Islamic Family Law.